Perlindungan Hukum Bagi Konsumen dan Pemegang Merek Terdaftar dari Pemanfaatan Merek Terkenal - See, Benedictus Renny (Jurnal Hukum Caraka Justitia, 2022)
The tendency of consumers to buy and use famous brands is a lifestyle for some people in this modern era. Considering that generally goods/services of well-known brands have a relatively more expensive sale value when compared to non-branded goods/services, so their existence is often used by parties who are not responsible for producing counterfeit goods/ services or selling counterfeit goods/services with us and utilize well-known brands. Therefore the use of a well-known trademark that has been registered by another unauthorized party will bring legal impact and loss to many parties, the first party that loses is the owner of the registered brand, and this will lead to fraudulent competition, the second party to be disadvantaged is the consumer community who buy and consume counterfeit products using well-known brands which should be protected from misleading behavior, other parties who are also disadvantaged by the use of well-known brands are the government/country in addition to not getting fees from the distribution of these well-known brands will also affect the country's image from the international business environment. In this study, the author tries to find out how the form of legal protection against "Famous brand holders" and against "Cosmetics" from the illegal use of famous brands and what needs to be done by the government to protect the practice of using registered (well-known) brands from the use of parties who are not entitled to.